2012
DOI: 10.1111/j.1349-7006.2012.02220.x
|View full text |Cite
|
Sign up to set email alerts
|

MARVELD1 inhibited cell proliferation and enhance chemosensitivity via increasing expression of p53 and p16 in hepatocellular carcinoma

Abstract: We have previously found that expression of MARVELD1 was remarkably downregulated in multiple tumor tissues, but unclear in hepatocellular carcinoma (HCC) and its function has not been explored yet. In the present study, to uncover the underlying mechanism of MARVELD1 in the pathogenesis and development of HCC, we investigated the expression pattern of MARVELD1 and its effect on tumor proliferation in HCC. The results indicated the frequent downregulation of MARVELD1 in clinic samples and cell lines of HCC res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
27
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 28 publications
5
27
2
Order By: Relevance
“…However, it has been reported that overexpression of MARVELD1 promotes the tumor sensitivity to chemotherapy in hepatocellular carcinoma, and our results seems conflicted with previous study [10]. To clarify this, we assessed the sensitivity of A549 cells to a serial chemo-drugs by overexpression of MARVELD1.…”
Section: Resultscontrasting
confidence: 75%
See 1 more Smart Citation
“…However, it has been reported that overexpression of MARVELD1 promotes the tumor sensitivity to chemotherapy in hepatocellular carcinoma, and our results seems conflicted with previous study [10]. To clarify this, we assessed the sensitivity of A549 cells to a serial chemo-drugs by overexpression of MARVELD1.…”
Section: Resultscontrasting
confidence: 75%
“…MARVELD1 is previously reported as a drug-resistant related protein [10]. Here, we validated the interaction between SREBP and MARVELD1 by co-immunoprecipitation (Figure 2A).…”
Section: Resultssupporting
confidence: 74%
“…To deplete the expression of MARVELD1 and UPF1, the siRNAs were used as follows: siMARVELD1 5’-r(AUU GGA ACC AGG CUU CUG G)-3’ [9], siMARVELD1-2 5’-r(CCU CAA GGA UUA CCC GCU C)-3’, siUPF1-1 5’-r(GAU GCA GUU CCG CUC CAU U)-3’ [15] and siUPF1-2 5’-r(GAG AAU CGC CUA CUU CAC U)-3’ [16]. …”
Section: Methodsmentioning
confidence: 99%
“…We previously reported that MARVELD1 localized to interphase cell nuclei and was downregulated in multiple tumor tissues [8]. The overexpression of MARVELD1 inhibited proliferation and enhanced chemosensitivity in hepatocellular carcinoma cells [9]. We also identified the interaction between MARVELD1 and importin β1 by liquid chromatography-tandem mass spectrometry analysis and coimmunoprecipitation in HeLa cells [10].…”
Section: Introductionmentioning
confidence: 99%
“…Zeng et al (2011) examined the function of MARVELD1 in mice and demonstrated that overexpression of mouse MARVELD1 inhibited cell proliferation, G1-phase arrest, and cell migration. In hepatocellular carcinoma, MARVELD1 is a tumor suppressor that regulates tumor growth and may be a potential biomarker for hepatocellular carcinoma therapy (Yu et al, 2012).…”
Section: Discussionmentioning
confidence: 99%